2023
DOI: 10.1007/s10530-023-03142-z
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical factors control invasive annual grass hot spots in the Mojave Desert

Abstract: Invasive annual grasses can promote ecosystem state changes and habitat loss in the American Southwest. Non-native annual grasses such as Bromus spp. and Schismus spp. have invaded the Mojave Desert and degraded habitat through increased fire occurrence, severity, and shifting plant community composition. Thus, it is important to identify and characterize the areas where persistent invasion has occurred, identifying where subsequent habitat degradation has increased. Previous plot and landscape-scale analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…They are one of the major factors inducing biotic homogenization [9], which is defined by an increase in genetic, taxonomic, or functional similarities across different sites over a predetermined period of time [10,11]. They alter the community structure and composition of recipient environments by displacing or suppressing the abundance and/or species richness of native species [12,13]. A study conducted by Forey et al [9] in a Fijian rainforest provides evidence in favor of this, showing that IAP Pinanga coronata (Blume) Blume decreased native species richness and Shannon diversity by 50% and 33%, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are one of the major factors inducing biotic homogenization [9], which is defined by an increase in genetic, taxonomic, or functional similarities across different sites over a predetermined period of time [10,11]. They alter the community structure and composition of recipient environments by displacing or suppressing the abundance and/or species richness of native species [12,13]. A study conducted by Forey et al [9] in a Fijian rainforest provides evidence in favor of this, showing that IAP Pinanga coronata (Blume) Blume decreased native species richness and Shannon diversity by 50% and 33%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Another study revealed that moss invasion reduced the functional diversity of carabid beetles while increasing spiders' functional similarity [12]. This occurred along with the dramatic change in species composition, i.e., abundance, richness, and diversity [12], ecosystem structure [13], and the functioning of an invaded ecosystem [5,16,20]. Because of this, it is claimed that biological invasion is one of the major causes of biodiversity loss and changes in ecosystem services provision globally [4,18,20,26].…”
Section: Introductionmentioning
confidence: 99%